Challenging Catholic School Resistance to GSAs with a Revised Conception of Scandal and a Critique of Perceived Threat - McDonough, Graham P. (Paideusis, 2014)
Educational leaders in Ontario’s publicly-funded Catholic schools typically resist establishing Gay-Straight Alliances (GSAs) on grounds that they contradict Catholic moral teaching and so cause scandal in the school. While the protection of GSAs in these schools is derived from recent provincial legislation, the government intervention has the potential to exacerbate religious-secular tensions in the school and society. This paper assumes that, in the Catholic Church’s current political climate, the only justifications for GSAs that will gain genuine traction and possibly deflate this tension descend from within Catholicism’s own tradition of thought and educational practice. The first part of the argument critiques the Catholic hierarchy’s traditional, narrow conception of scandal, and replaces it with a revised, broader conception from within Catholic theology in which the traditional marginalization of lesbian, gay, bisexual, transgendered, queer, and questioning (LGBTQ) students is the true scandal. These two frameworks are used to analyze inconsistencies between the resistance Catholic schools show toward LGBTQ students wanting to establish GSAs, and the welcoming attitude they display toward pregnant and parenting students. The second part of the argument reveals that the main reason for this difference is that Church officials perceive all LGBTQ organizations as threats to their authority, and this perception is extended to GSAs. This internal critique provides sufficient reason to reverse the current negative Catholic evaluations of GSAs.